Perceived entrapment predicts first-onset suicidal ideation: A longitudinal study among medical students in China - Suping Wang; Suping Wang; Ting Wei; Rui Zhu; Sicong Li; Xinyi Liu; Yong Cai; Yong Cai; Ruijie Gong; Ruijie Gong; Ruijie Gong (Frontiers Media S.A., 2023)
IntroductionThe prevalence of suicidal ideation among medical students is high. Evidence indicates that feelings of entrapment are a predictor of suicidal ideation. In this study, we aimed to (1) investigate the prevalence of first-onset suicidal ideation among Chinese medical students and (2) explore the predictive effects of perceived entrapment on first-onset suicidal ideation.MethodsThis longitudinal study was conducted between 2018 and 2019 among 211 newly enrolled medical students in Shanghai. Using an anonymous questionnaire, we collected information on sociodemographic (sex, major, parents' income, and academic performance) and psychological (entrapment, depression, loneliness, defeat, social support, and interpersonal needs) variables as well as suicidal ideation. Participants were divided into four subgroups based on their exposure to entrapment (control, new-onset, reduced, and persistent). The primary outcome, first-onset suicidal ideation, was defined as suicidal ideation absent at baseline but present at follow-up.ResultsIn total, 54.98% of participants (116/211) were women, and 76.78% (162/211) majored in clinical medicine. In the follow-up survey, 6.16% of participants (16/211) reported first-onset suicidal ideation, 17.54% (37/211) reported new-onset entrapment, and 12.80% (27/211) reported persistent entrapment during follow-up. Compared with the control group who reported no perceived entrapment at baseline and follow-up, participants who reported new-onset entrapment had the highest risk of new-onset suicidal ideation [odds ratio (OR) = 14.700, 95% confidence interval (CI) = 2.906-74.364; adjusted OR = 8.798; 95% CI = 1.588-48.757; multivariate OR = 8.238, 95% CI = 1.394-48.693).ConclusionNew-onset entrapment can significantly predict suicidal ideation. Therefore, greater attention is needed for new-onset entrapment, such as intervention for suicidal ideation.